Exploring the Use of Entomopathogenic Nematodes and the Natural Products Derived from Their Symbiotic Bacteria to Control the Grapevine Moth, Lobesia botrana (Lepidoptera: Tortricidae) - Ignacio Vicente-Díez; Rubén Blanco-Pérez; Maryam Chelkha; Miguel Puelles; Alicia Pou; Raquel Campos-Herrera (Insects, 2021)
The European grapevine moth (EGVM) Lobesia botrana (Lepidoptera: Tortricidae) is a relevant pest in the Palearctic region vineyards and is present in the Americas. Their management using biological control agents and environmentally friendly biotechnical tools would reduce intensive pesticide use. The entomopathogenic nematodes (EPNs) in the families Steinernematidae and Heterorhabditidae are well-known virulent agents against arthropod pests thanks to symbiotic bacteria in the genera Xenorhabdus and Photorhabdus (respectively) that produce natural products with insecticidal potential. Novel technological advances allow field applications of EPNs and those bioactive compounds as powerful bio-tools against aerial insect pests. This study aimed to determine the viability of four EPN species (Steinernema feltiae, S. carpocapsae, S. riojaense, and Heterorhabditis bacteriophora) as biological control agents against EGVM larval instars (L1, L3, and L5) and pupae. Additionally, the bioactive compounds from their four symbiotic bacteria (Xenorhabdus bovienii, X. nematophila, X. kozodoii, and Photorhabdus laumondii subsp. laumondii, respectively) were tested as unfiltered ferment (UF) and cell-free supernatant (CFS) against the EGVM larval instars L1 and L3. All of the EPN species showed the capability of killing EGVM during the larval and pupal stages, particularly S. carpocapsae (mortalities of ~50% for L1 and >75% for L3 and L5 in only two days), followed by efficacy by S. feltiae. Similarly, the bacterial bioactive compounds produced higher larval mortality at three days against L1 (>90%) than L3 (~50%), making the application of UF more virulent than the application of CFS. Our findings indicate that both steinernematid species and their symbiotic bacterial bioactive compounds could be considered for a novel agro-technological approach to control L. botrana in vineyards. Further research into co-formulation with adjuvants is required to expand their viability when implemented for aboveground grapevine application.